The Effectiveness of Using WhatsApp in English Language Teaching during the Covid-19 Pandemic for Junior High School Students - Rahayu Malilla; Irwandi Irwandi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2022)
This research is motivated by the change of the learning system from face-to-face (offline system) to online system caused by the COVID-19 pandemic. Yet, the purpose of this study was to determine the effectiveness of teaching English using WhatsApp during the COVID-19 pandemic, both for teaching receptive skills and productive skills using WhatsApp. This research used a descriptive quantitative method. The population in this study was all 7th-grade students at SMPN 2 Tanjung Raya. The sample in this study was all 7th-grade students of SMPN 2 Tanjung Raya as many as 50 students. The data collection technique used total sampling. The data were collected using the questionnaire. This study found that in general, on teaching English receptive skills and productive skills through distance were categorized as effective with a percentage of 79.9%. It means, for receptive skills in listening with an average of 80.6% and reading with an average of 82.4%. And teaching English productive skills with an average of 80.1% speaking and 76.6% writing. It is concluded that the use of the WhatsApp application as an English learning medium by English teachers during the Covid-19 pandemic was effective in teaching four English skills.